Toksisitas Ekstrak Daun Kopasanda (Chromolaena Odorata) Terhadap Larva Artemia Salina Leach - Sumardi (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
ABSTRACT Leaf kopasanda (Chromolaena odorata L. King & H.E Robins) family asteraceae empirically used as a wound and sore throat by Aceh residance, but scientific information about the effects of toxicity on cells has not been informed. The method used is phytochemical screening by using appropriate chemical detection reagents and continued with the search profile for extract using thin layer chromatography (TLC) as well as toxicity test of crude extract and its partition to shrimp larvae (Artemia salina Leach). Chemical content of extracts showed the presence of flavonoids, saponins, triterpenoids, alkaloids and tannins. The stain profile on TLC plate with silica gel GF254 as stationary phase showed the best stain by using the mobile phase on crude extract ethanol and its partition ethyl acetate, n-hexane and water were respectively n-heksan : etil asetat (3:7), n-heksan : etil asetat (7:3); n-heksan : etil asetat (2:8). their toxicity effects showed a low toxic category. C. odorata extracts have potentially safe and can be developed in aspects of biological activity.